2009
DOI: 10.1016/j.amepre.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Fat Mass Index, Fat Free–Mass Index, and Waist Circumference in Children

Abstract: Background Body composition and fat distribution change dramatically during adolescence. Data based on longitudinal studies to describe these changes are limited. The aim of this study was to describe age-related changes in fat free–mass index (FFMI) and fat mass index (FMI), which are components of BMI, and waist circumference (WC) in participants of Project HeartBeat!, a longitudinal study of children. Methods Anthropometric measurements and body composition data were obtained in a mixed longitudinal study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 18 publications
(23 reference statements)
7
54
1
6
Order By: Relevance
“…Although BMI is a useful surrogate for body composition of a group, our data suggest in agreement with others that the relationship of BMI to body composition varies through childhood by age, sex (Demerath et al, 2006;Wright et al, 2010) and ethnicity (Eissa et al, 2009). What we add to the literature is the marked difference between the growth trajectories of Māori and European children.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Although BMI is a useful surrogate for body composition of a group, our data suggest in agreement with others that the relationship of BMI to body composition varies through childhood by age, sex (Demerath et al, 2006;Wright et al, 2010) and ethnicity (Eissa et al, 2009). What we add to the literature is the marked difference between the growth trajectories of Māori and European children.…”
Section: Resultssupporting
confidence: 76%
“…A strength of the bioimpedance measurement was that the prediction equation was developed in Māori, Pacific and European children with a wide range of body fatness but it recognised that measurements of BF derived from bioimpedance measures are more applicable to group data rather than individual. We consider the sample size of this study to be insufficient to estimate the individual differences and the influence of other confounders, but, in agreement with other longitudinal studies, the main effects by gender, age (Demerath et al, 2006;Wright et al, 2010) and ethnicity (Eissa et al, 2009) on the relationship between BMI and BF are clear. Between 1991and 1995Eissa et al (2009 showed that black girls between age 10 and 12 years increased FMI by one unit, whereas the comparable change in our [2004][2005][2006] Māori girls was two units, which may be related to earlier puberty.…”
Section: Tracking Body Mass Indices E Rush Et Almentioning
confidence: 75%
See 1 more Smart Citation
“…29 The use of this index, which is promising but requires a valid assessment of body composition by the pediatrician, is increasingly under evaluation. [30][31][32] Perspective Reference intervals of FMI versus FFMI, for adults, children and teenagers, can be used as indicative values for the evaluation of nutritional status (degree of overnutrition or undernutrition) of apparently healthy subjects. It can also provide complementary information to the classical expression of body composition reference values.…”
Section: Ffmi and Fmi In Childrenmentioning
confidence: 99%
“…It is important to periodically survey populations at risk in order to determine the need for appropriate interventions. 2 Adolescence is one of the four known sensitive periods in life for the development of obesity, the other three being intrauterine life, infancy and ages 5 -7 years. 3 Often, body mass index (BMI) is used as proxy for assessing excessive accumulation of body fat, partly because of ease of measurement.…”
Section: Introductionmentioning
confidence: 99%